The impact of community-based arts and health interventions on cognition in people with dementia: a systematic literature review - Young, Rhea; Camic, Paul M.; Tischler, Victoria (Aging & mental health, 2016)
Objectives: Dementia is a progressive condition, affecting increasing numbers of people, characterised by cognitive decline. The current systematic review aimed to evaluate research pertaining to the impact of arts and health interventions on cognition in people with dementia. Method: A literature search was conducted utilising PsychInfo, Cochrane Reviews, Web of Science, Medline and British Humanities Index databases. Seventeen studies were included in the review, including those related to literary, performing and visual arts. Results: The review highlighted this as an emerging area of research with the literature consisting largely of small-scale studies with methodological limitations including lack of control groups and often poorly defined samples. All the studies suggested, however, that arts-based activities had a positive impact on cognitive processes, in particular on attention, stimulation of memories, enhanced communication and engagement with creative activities. Conclusion: The existent literature suggests that arts activities are helpful interventions within dementia care. A consensus has yet to emerge, however, about the direction for future research including the challenge of measurement and the importance of methodological flexibility. It is suggested that further research address some of these limitations by examining whether the impact of interventions vary depending on cognitive ability and to continue to assess how arts interventions can be of use across the stages of dementia.